ATMOSPHERIC CARBON DIOXIDE MEASUREMENTS AT SYOWA STATION, ANTARCTICA, 1984-1988 - アオキ, シュンジ; ナカザワ, タカキヨ; ムラヤマ, ショウヘイ; フカボリ, マサシ; ヤマノウチ, タカシ; ムラヤマ, ハルタ; シオバラ, マサタカ; カワグチ, サダオ; タナカ, マサユキ; AOKI, Shuhji; NAKAZAWA, Takakiyo; MURAYAMA, Shohei; et al. (National Institute of Polar Research, 1992)
P(論文) Precise and continuous measurements of atmospheric CO_2 concentration have been continued at Syowa Station (69°00'S, 39°35'E), Antarctica since February 1984. Diurnal CO_2 variation was hardly observable throughout the year. The secular CO_2 trend was variable with time, showing slow increase in 1984,1986 and 1988 and rapid increase in 1985 and 1987. The annual CO_2 increase was remarkable, especially in 1987,which may be related to the 1987 ENSO event. The average rate of annual CO_2 increase over the last 5 years was about 1.6 ppmv yr^<-1>. The average seasonal CO_2 cycle showed minimum and maximum concentrations in mid-April and in early October, respectively. Its peak-to-peak amplitude was about 1.1 ppmv for the period 1984-1988. The seasonal cycle was variable from year to year, but there was no indication of long-term amplitude increase. It was found that irregular CO_2 variations with amplitudes of about 0.2 ppmv and with periods of a few tens of days have high correlation with air mass exchange by synoptic scale weather disturbances. departmental bulletin paper